Equivalent discontinuum analysis of stress and displacement in underground rock masses. (February 2023) - Li, Meiyu; Ma, Guowei; Li, Tuo; Chen, Yun; Wang, Huidong
Abstract: The complexity and high frequency of fractures in rock masses make discrete fracture network (DFN) models suffer from burdensome computational consumption when every fracture is explicitly simulated. Meanwhile, the uncertainty in the spatial distribution of fractures also leads to the unnecessary explicit simulation of small fractures to achieve more accurate results. In this study, an equivalent discontinuum analysis (EDA) method is proposed to deal with complexly fractured rock masses in the deep underground. An equivalent discrete fracture network (E-DFN) with simple geometric configurations is extracted based on a defined significance index of fractures. The influence of fractures that are neglected in E-DFNs is superposed on the remaining fractures by reassigning their material properties. Using the proposed EDA method, the anisotropy of the deformation modulus of the original DFN model is well represented by the E-DFN models. Compared with the equivalent continuum and discontinuum models, the E-DFN models with reassigned fracture properties have a better potential for maintaining stress variability and displacement discontinuity in rock masses. Highlights: An EDA method is proposed to deal with complexly fractured rock mass. E-DFN is extracted from DFN according to a fracture significance index. The effect of insignificant fractures is compensated in E-DFN. The E-DFN and DFN model share similar local and global characteristics.